2019
DOI: 10.1051/0004-6361/201834557
|View full text |Cite
|
Sign up to set email alerts
|

Two new free-floating or wide-orbit planets from microlensing

Abstract: Planet formation theories predict the existence of free-floating planets that have been ejected from their parent systems. Although they emit little or no light, they can be detected during gravitational microlensing events. Microlensing events caused by rogue planets are characterized by very short timescales tE (typically below two days) and small angular Einstein radii θE (up to several μas). Here we present the discovery and characterization of two ultra-short microlensing events identified in data from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 72 publications
(76 reference statements)
3
56
0
Order By: Relevance
“…8 Typically the source radius crossing time as defined by r q m = = t t E rel * * is used as a proxy for the timescale of the event (e.g., Skowron et al 2011); however, we account for nonzero impact parameter u 0, * similar to Mróz et al (2019a). We follow their definition, except we use the variable t c instead for their Equation (A1).…”
Section: Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Typically the source radius crossing time as defined by r q m = = t t E rel * * is used as a proxy for the timescale of the event (e.g., Skowron et al 2011); however, we account for nonzero impact parameter u 0, * similar to Mróz et al (2019a). We follow their definition, except we use the variable t c instead for their Equation (A1).…”
Section: Yieldmentioning
confidence: 99%
“…Indeed, quite recently, multiple well-characterized, extremely short microlensing events have been discovered. Mróz et al (2018Mróz et al ( , 2019a, and Mróz et al (2020) together report a total of four FFP candidates, two of which had timescales consistent with Earth-or Neptune-mass lenses. Han et al (2020a) report the discovery of three events consistent with brown dwarf mass lenses (masses of ∼0.04 M e ), of which two are isolated and one is in a near-equal-mass binary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From detailed investigation, it is found that the event is produced by a wide-separation planet and the analyses will be presented in a separate paper. Mróz et al (2018Mróz et al ( , 2019, respectively. They pointed out that the lens of OGLE-2016-BLG-1540 was likely to be a Neptunemass free-floating planet in the Galactic disk and the lens of OGLE-2017-BLG-0560 is either a Jupiter-mass free-floating planet in the disk or a BD in the bulge.…”
Section: Event Selectionmentioning
confidence: 99%
“…Gravitational microlensing is potentially a powerful tool for probing isolated objects with various masses such as free-floating planets, brown dwarfs, low-mass stars, and black holes. At the low-mass end, microlensing has detected several free-floating planet candidates based on their short microlens timescale, t E 2 days (Sumi et al 2011;Mróz et al 2017Mróz et al , 2018Mróz et al , 2019, including a few possible Earth-mass objects. Such discoveries are crucial for testing theories about the origin and evolution of free-floating planets (Veras & Raymond 2012;Pfyffer et al 2015;Ma et al 2016; Barclay et al 2017;Clanton & Gaudi 2017).…”
Section: Introductionmentioning
confidence: 99%